Agricultural mechanization in Tanzania - Mrema, Geoffrey C.; Kahan, David G.; Agyei-Holmes, Andrew (International Food Policy Research Institute, 2020)
Tanzania has seen a slow but steady growth in agricultural mechanization over the past few decades. The country’s mechanization growth trend is fairly consistent with patterns elsewhere, with both agroecological and socioeconomic conditions as key determinants of increased mechanization. The private sector has often led the development of machinery markets and service providers to meet mechanization demand, including emerging medium- to large-scale farmers serving as self-financed owners of tractors providing custom hiring services. Despite such progress, several knowledge gaps exist regarding the roles of various factors in mechanization, including land tenure policy, and regarding identification of the roles of governments in effectively supporting the private sector toward further mechanization growth.